The Effect of Earning Per Share, Debt To Equity Ratio, Price To Book Value Towards Stock Prices At PT. Airasia Indonesia, Tbk - Wulandari Wulandari; Aris Munandar (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
The research objective is to prove and explain the effect of eraning per share, debt to equity ratio, price to book value on the stock price corporate AirAsia Indonesia.The sample in this study is Pt. AirAsia Indonesia quarterly financial report data for 3 years, from 2018-2020 registered on the stock exchange. Linear multiple regression used in this study to answer the research underlying problems. The conclusion of this study is that eraning per share affects stock prices, debt to equity ratio affects stock prices,price to book value has no effect on stock prices, and earnings per share, debt to equity ratio, price to book value affect stock prices at Pt. AirAsia Indonesia, tbk.